Dengue viral infections. Issue 948 (5th October 2004) - Malavige, G N; Fernando, S; Fernando, D J; Seneviratne, S L
Abstract : Dengue viral infections are one of the most important mosquito borne diseases in the world. They may be asymptomatic or may give rise to undifferentiated fever, dengue fever, dengue haemorrhagic fever (DHF), or dengue shock syndrome. Annually, 100 million cases of dengue fever and half a million cases of DHF occur worldwide. Ninety percent of DHF subjects are children less than 15 years of age. At present, dengue is endemic in 112 countries in the world. No vaccine is available for preventing this disease. Early recognition and prompt initiation of appropriate treatment are vital if disease related morbidity and mortality are to be limited. This review outlines aspects of the epidemiology of dengue infections, the dengue virus and its mosquito vector, clinical features and pathogenesis of dengue infections, and the management and control of these infections.